Effect of Al vacuum annealing prior to a‐Si deposition on aluminum‐induced crystallization. Issue 12 (4th November 2015) - Tankut, Aydin; Karaman, Mehmet; Yildiz, Ilker; Canli, Sedat; Turan, Rasit
Abstract : Aluminum‐induced crystallization (AIC) experiments were carried out in order to investigate the influence of vacuum annealing of the Al layer at 500 °C prior to deposition of e‐beam evaporated amorphous silicon (a‐Si). A control sample set using the identical deposition sequences but without the Al vacuum anneal was also produced as reference. Analysis revealed that after vacuum annealing, the Al grain size increases significantly. The surface Al‐oxide layer thickness is reduced, however, the Al‐oxide to metallic Al ratio is increased in this layer. Following a‐Si deposition, the a‐Si/Al/SiN x /glass stacked samples were annealed in N2 atmosphere at temperatures between 420 and 450 °C. It was seen that the crystal growth rate in the samples with vacuum‐annealed Al is significantly reduced compared to the control samples, due to the reduction of Al grain boundary density.